The Effect of Corn Flour (Zea Mays Indurate) Substitution on the Physical Properties and Sensory Quality of Mini Dry Pastel Skin - Fathimah Azzahro; Yeni Yulianti; Sachriani (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2026)
This study aimed to analyse the effect of corn flour substitution on physical properties, including brittleness and oil absorption, as well as sensory quality tests covering colour, aroma, taste, and texture in mini dry pastel skins. The research was conducted from December 2024 to June 2025 at the Pastry Bakery Laboratory for sensory quality testing, while physical properties were tested at the Food Engineering Laboratory, Jakarta State University. This type of research is classified as quantitative research using the experimental method, with corn flour substitution treatments of 20%, 30%, and 40%. Sampling was conducted randomly, with each panellist receiving one randomly selected sample, coded only by the researcher. Sensory quality testing was conducted on 15 moderately trained panellists for each sample. Physical properties were tested using a Texture Profile Analyser for brittleness and oil absorption, by calculating the difference between the amount of oil absorbed before and after the baking paper was exposed to it. The physical property analysis technique used the Anova test, followed by the Duncan test, while the sensory quality analysis used the Kruskal-Wallis test, followed by the Tukey test. The brittleness test results showed a significant effect, with the best results obtained at 30% treatment, while there was no significant effect on oil absorption. Sensory quality test results for colour, corn aroma, savoury taste, corn taste, and texture (crispness) showed no significant effect. The results of this study recommend a percentage of 30% as a reference for further research, as it is considered to be in line with the characteristics of a crispy but not too brittle pastel crust and for the optimal use of corn flour. Keywords: pastel crust, corn flour, physical properties, sensory quality test